Implantable Cardioverter Defibrillators in Patients With Continuous Flow Left Ventricular Assist Devices: Utilization Patterns, Related Procedures, and Complications - Paulino A. Alvarez; Brett W. Sperry; Antonio L. Pérez; Dmitry M. Yaranov; Varinder Randhawa; Jacob Luthman; Daniel J. Cantillon; Randall C. Starling (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2019)
Background The effect of implantable cardioverter defibrillators (ICD) in patients with continuous flow left ventricular assist devices (LVADs) on outcomes has not been evaluated in a randomized clinical trial. Methods and Results This is a retrospective single‐center study that included patients who underwent continuous flow LVAD implantation at the Cleveland Clinic between October 2004 and March 2017. Patients were evaluated according to the presence or absence of ICD at the time of LVAD insertion. Among 486 patients in the study cohort, 387 (79.6%) had an ICD before LVAD insertion. Patients with ICD before LVAD were older and had lower use of pre‐LVAD inotropes, extracorporeal membrane oxygenation, and mechanical ventilation. There were 81 patients (21.4% of patients with ICD) who required 93 procedures after LVAD: 74 generator exchanges, 12 lead revisions, and 7 complete system removals because of infection. Of the 99 patients without ICD, 52 (53%) underwent ICD implantation: 29 for primary prevention and 23 for secondary prevention. Patients were followed for a median of 401 (interquartile range 150–966) days. The presence of a pre‐LVAD ICD was not associated with mortality in a multivariable model (hazard ratio 1.19, 95% CI 0.73–1.93, P=0.492), nor was the presence of an ICD at any point when analyzed as a time‐varying covariate (hazard ratio 1.05, 95% CI 0.50–2.20, P=0.907). Conclusions There is no apparent mortality benefit associated with an ICD in a contemporary cohort of patients with continuous flow LVADs to balance considerable morbidity involving ICD‐related procedures and complications.